Factors affecting the use of mhealth home workout – no equipment application in indonesia with an intention to use approach - Damar Wulan; Ahmad Shalahuddin; Wenny Pebrianti; Ramadania Ramadania; Syahbandi Syahbandi (Jurnal Mantik, 2023)
This study's objective is to identify the predictors of usage intention among Indonesia's Generation Z. Mobile health (mHealth) can contribute to Indonesia's public health system. A sample of 375 Generation Z individuals who own a smartphone and have information about the mHealth application "Home Workout – No Equipment" was collected via an online questionnaire. The central emphasis of this research concerns a range of substantial variables as outlined in the Unified Theory of Acceptance and Use of Technology (UTAUT). Utilizing two-step structural equation modeling, the hypothesized relationships were examined, and the measurement model was validated. Significant and positive influences on attitude are exerted by performance expectancy, facilitating conditions, and social influence; on the other hand, effort expectancy exerts a substantial and negative impact. The impact of attitude on usage intention is substantial and favorable. Technophobia does not significantly moderate the relationship between effort expectancy and performance expectancy and attitude. By developing a model that integrates attitude variables as predictors of usage intention, this study addresses a research gap by establishing a framework for assessing Generation Z's intention to use mHealth applications in Indonesia. This research can help application developers and health service providers better understand the younger generation's preferences and needs and support efforts to improve public health in Indonesia